Hubungan Dukungan Sosial dengan Stres Akademik pada Mahasiswa Keperawatan Tingkat Akhir - Nababan, Cindy; Rantung, Jeanny (NUTRIX, 2026)
This study aimed to determine the relationship between social support and academic stress among final-year nursing students at Universitas Advent Surya Nusantara. This research used a quantitative approach with a descriptive analytic design and a cross-sectional method. The population consisted of 37 final-year nursing students, and total sampling was applied. Data were collected using the Multidimensional Scale of Perceived Social Support (MSPSS) and the Perceived Academic Stress Scale (PASS). Data analysis was conducted using univariate and Spearman Rank correlation tests. The results showed that most respondents had high social support (73.0%) and experienced high academic stress (78.4%). The correlation analysis revealed a correlation coefficient (r) of 0.096 with a p-value of 0.574 (p > 0.05), indicating that there was no significant relationship between social support and academic stress. These findings suggest that social support is not the main factor influencing academic stress among final-year students. Therefore, efforts to reduce academic stress should also consider other factors such as coping ability, time management, and academic support from institutions. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial dengan stres akademik pada mahasiswa keperawatan tingkat akhir di Universitas Advent Surya Nusantara. Penelitian ini menggunakan pendekatan kuantitatif dengan desain deskriptif analitik dan rancangan cross-sectional. Populasi penelitian berjumlah 37 mahasiswa dengan teknik total sampling. Pengumpulan data menggunakan kuesioner Multidimensional Scale of Perceived Social Support (MSPSS) dan Perceived Academic Stress Scale (PASS). Analisis data dilakukan secara univariat dan bivariat menggunakan uji korelasi Spearman Rank. Hasil penelitian menunjukkan bahwa sebagian besar responden memiliki dukungan sosial tinggi (73,0%) dan mengalami stres akademik tinggi (78,4%). Hasil uji korelasi menunjukkan nilai r = 0,096 dengan p-value = 0,574 (p > 0,05), sehingga tidak terdapat hubungan yang signifikan antara dukungan sosial dan stres akademik. Hal ini menunjukkan bahwa dukungan sosial bukan merupakan faktor utama yang mempengaruhi stres akademik pada mahasiswa tingkat akhir. Oleh karena itu, diperlukan perhatian terhadap faktor lain seperti kemampuan coping, manajemen waktu, dan dukungan akademik dari institusi Pendidikan.